Satisfacción Laboral del Profesorado de Educación Infantil, Primaria, Secundaria y Formación Profesional con las Instalaciones y Recursos del Centro, en Función de Variables Sociodemográficas y de Cargos de Responsabilidad - González Álvarez, María (2022)
The main goal of this paper is to carry out an exploratory study on the job satisfaction of preschool, primary, secondary and vocational training teachers about the work environment, facilities and resources of the school according to different sociodemographic variables and responsibility positions. The information was collected among a sample of teachers from different regions of Spain, using an online questionnaire specifically written for this research. The questionnaire was answered by 2738 teachers. Cronbach reliability coefficient is .80. Descriptive analysis, media differences and multivariate analysis were performed. According to the results, teachers rate their general job satisfaction as medium-high. About the work environment, facilities and resources of the school is rated as medium-high.